Future Cities. Proceedings of the 28th Conference on Education in Computer Aided Architectural Design in Europe. September 15-18, 2010 Zurich. Switzerland ETH Zurich. eCAADe 2010. - (:unkn) unknown (vdf Hochschulverl., 2010)
Einige Beiträge sind curricularen Fragen gewidmet, und bewegt sich vorwiegend im universitären Ausbildungsbereich in den Fächern Architektur und Städtebau/Stadtplanung. Andere Beiträge stellen neue Entwurfsmethoden und Strategiekonzepte vor, mit Themen wie interaktive Architekturen, selbstorganisierende Karten, Softskins. Generatives und parametrisches Entwerfen sowie Software-Entwicklungen. Der Themenkreis Simulation und Visualisierung, Voraussage und Evaluation leitet über zu Beiträgen über kooperative Entwurfsstrategien und zu Programmen für städtebauliches Entwerfen und über die Integration von Darstellungen virtueller Realität in Gebäudemanagementprogramme und andere Programme.

For the first time in human history, more than 50% of the world's population lives in urban regions. Cities are the largest, most complex, and most dynamic man-made systems. They are vibrant centers of cultural life and engines that drive the global economy. Contemporary cities are environmentally, socially, and economically unsustainable. The quality of urban life is threatened by such factors as pollution, rising temperatures, limited resources, congestion, social inequalities, aging of large sectors of the world population, poverty, informality, crime, and economic imbalances. The overall planning of future cities is a challenge that can only be faced by interdisciplinary teams combining multitudes of backgrounds and expertise.
Keywords: Stadtplanung; Städtebau; Architektur; Bauwerksplanung; Planungsmodell; Entwurf; CAD; Design; Modell; EDV-Software; Simulation